2020
DOI: 10.1101/2020.06.21.163923
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Draft genome sequence of the pulse crop blackgram [Vigna mungo(L.) Hepper] reveals potential R-genes

Abstract: Blackgram [Vigna mungo (L.) Hepper] (2n = 2x = 22), an important Asiatic legume crop, is a major source of dietary protein for the predominantly vegetarian population. Here we construct a draft genome sequence of blackgram, for the first time, by employing hybrid genome assembly with Illumina reads and third generation Oxford Nanopore sequencing technology. The final de novo whole genome of blackgram is ~ 475 Mb (82 % of the genome) and has maximum scaffold length of 6.3 Mb with scaffold N50 of1.42 Mb. Genome … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The segregation of 3 indeterminate: 1 determinate types in MF 2 generation suggested the trait to be under the governance of a single recessive gene for TFL in cowpea. [55] reported that VuTFL1 is the candidate gene responsible for the TFL type in cowpea, and also this gene family was well established in Arabidopsis [56], peas [28] and soybean [57]. In the present study, the VuTFL1 gene was sequenced in mutants and wild-type plants.…”
Section: Discussionmentioning
confidence: 76%
“…The segregation of 3 indeterminate: 1 determinate types in MF 2 generation suggested the trait to be under the governance of a single recessive gene for TFL in cowpea. [55] reported that VuTFL1 is the candidate gene responsible for the TFL type in cowpea, and also this gene family was well established in Arabidopsis [56], peas [28] and soybean [57]. In the present study, the VuTFL1 gene was sequenced in mutants and wild-type plants.…”
Section: Discussionmentioning
confidence: 76%
“…The genome annotation contained 32,729 predicted gene models, of which 29,411 (89.86%) were protein-coding genes. Shortly, Souframanien et al. (2021) constructed a draft genome sequence of 502 Mb of black gram variety Pant U-31 with 42,115 predicted genes.…”
Section: Genomicsmentioning
confidence: 99%
“…The genome annotation contained 32,729 predicted gene models, of which 29,411 (89.86%) were protein-coding genes. Shortly, Souframanien et al (2021) constructed a draft genome sequence of 502 Mb of black gram variety Pant U-31 with 42,115 predicted genes. Ambreen et al (2022) constructed a draft reference-guided genome assembly of black gram genotype 'Uttara' (IPU 94-1; known for its high resistance to Mungbean Yellow Mosaic Disease), with a cumulative size of 454 Mb and 28,881 predicted genes, of which 444 Mb was anchored on 11 chromosomes.…”
Section: Indiamentioning
confidence: 99%
“…While the LEA gene family also plays an important role in growth and development under multiple stress conditions, the study of this gene family in Vigna is still lacking. Many Vigna species are now sequenced, such as mung bean ( Kang et al, 2014 ), adzuki bean ( Kang et al, 2015 ), cowpea ( Lonardi et al, 2019 ), beach pea ( Singh et al, 2019b ), moth bean ( Takahashi et al, 2019 ), and black gram ( Souframanien et al, 2020 ), with their sequence data available in the public database and can be accessed for analysis. Keeping this in view, this experiment was conducted to survey LEA genes and study their comparative structural diversity analysis in mung bean, adzuki bean, and cowpea.…”
Section: Introductionmentioning
confidence: 99%